EKONOMI SUMBER DAYA ALAM DAN FLUKS KARBON HUTAN: TINJAUAN SISTEMATIS TERHADAP PENGELOLAAN HUTAN BERKELANJUTAN - FredySyah Putra; Mario Purba; Wendi Rehan Situmorang; Bonaraja Purba (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the relationship between natural resource economics and forest carbon flux in supporting sustainable forest management through a qualitative approach using the Systematic Literature Review (SLR) method. Forests play a crucial role not only as an economic resource but also as an ecosystem capable of absorbing and storing carbon from the atmosphere. Increasing deforestation, land conversion, and overexploitation of forest resources have led to environmental damage and increased carbon emissions. This study analyzed various national and international scientific publications published between 2016 and 2025 related to forest carbon flux, environmental economics, and sustainable forest management. The results show that sustainable forest management positively contributes to carbon emission reduction, ecosystem conservation, and long-term economic sustainability. In addition, the application of environmental economic instruments such as carbon trading, forest rehabilitation, and payments for environmental services can support climate change mitigation and increase community participation in forest conservation. This study concludes that the integration of economic and environmental aspects is an important factor in realizing sustainable forest governance and development oriented towards environmental sustainability